Efficacy and safety of sulforaphane-loaded emulsomes as tested on MCF7 and MCF10A cells - Karroum, Reem; Üçışık, Mehmet Hikmet (My University, 2024)
Objectives: Sulforaphane is well-known for its anti-cancer properties particularly against breast, skin and prostate cancers. High sensitivity of sulforaphane to oxygen, heat, and alkaline conditions, as well as its poor oral bioavailability and water instability limit its use in medicine. In this study, we aim to overcome the prementioned limitations by encapsulating sulforaphane within a lipid-based drug delivery system, known as emulsome, and investigate the anti-cancer features of the attained formulation. Methods: The stability and dispersity of the formulation were assessed sequentially by zeta sizer, scanning electron microscopy and confocal laser scanning microscopy. Cell culture studies were performed to evaluate the anticancer activity of the formulation. Results: Sulforaphane-loaded emulsomes with an average particle size of 246.0±14.1 nm, an average zeta potential of −23.5±2.4 mV and a polydispersity index of around 0.38 were produced. Encapsulations up to 0.036 mg/mL sulforaphane concentration was achieved. When MCF7 breast cancer cells were treated with sulforaphane-loaded emulsomes, a significant decrease was observed in proliferation of the cells along 72 h. In control group, emulsomes were found safe as tested at same concentrations on MCF-10a healthy cells. Applied as dissolved in DMSO, free sulforaphane with an IC50 value of 1.2 µM was more effective against MCF7 cells than sulforaphane-loaded emulsome formulation having a IC50 value 21.1 µM. Conclusions: Sulforaphane-loaded emulsomes were obtained as stable, moderately disperse suspensions. Delivery of the bioactive compound into the cells were achieved. Yet, its biological activity remained behind its free form.
Keywords: Limited Bioavailability; Lipid Nanoparticles; Mcf7 Breast Cancer Cell Line; Nanomedicine; Sulforaphane